Thumping Behaviour in the Rabbit - Black, Stephen Lawrence (My University, 1968)
Electrical stimulation of areas in the diencephalon and central grey of the conscious rabbit produces a response of thumping the ground with the hindfeet. The response is not elicitable from the neocortex, striatum or internal capsule. Thumping movements occur mainly after offset of the eliciting stimulus and the likelihood of a response decreases regularly with time, suggesting the decay of a central excitatory state.
Central stimulation which produces thumping behaviour tends to be aversive in tests for self-stimulation. Further, the behaviour can be elicited by peripheral electric shock. Therefore thumping behaviour may be a sign of fear in the rabbit.
Keywords: thumping, behaviour, rabbit, neocortex